Odorless Glutathione Microneedle Patches for Skin Whitening - Lee, Yechan (Pharmaceutics, 2020)
Glutathione is a natural anti-aging substance that prevents the oxidation of protein thiols from reactive oxygen species. In the pharmaceutical industry, reduced glutathione (GSH) has been widely used for skin whitening due to its ability to inhibit tyrosinase. However, its poor permeability and foul odor limit its use in skin applications. Herein, we report a GSH-loaded dissolving microneedle (MN) patch prepared with hyaluronic acid (HA) that enables enhanced permeation across the skin and reduces the foul odor of GSH. HA was selected to prepare odorless GSH solutions and used for MN fabrications as a carrier of GSH. GSH-loaded MN (GSH-MN) arrays prepared from MN-forming solution containing up to 10% GSH showed good pattern uniformity and appropriate mechanical properties for insertion into the skin. The GSH-MNs with a loading capacity of 17.4% dissolve within 10 min following insertion into porcine skin and release the loaded GSH without being oxidized. This new approach combines functional biopolymers to reduce the characteristic GSH odor and advanced transdermal delivery based on MN technology to enhance skin permeation without pain. We believe this technique could expand the application of GSH in many cosmeceutical fields.